2019
DOI: 10.1111/pin.12806
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of the common bile duct: A case report with genomic profiling

Abstract: Squamous cell carcinoma of the extrahepatic bile ducts is a very rare type of cancer with a virtually unknown pathogenesis. We present the case of a 66‐year‐old woman who underwent a pancreaticoduodenectomy with the postoperative diagnosis of squamous cell carcinoma of the common bile duct. Microscopically, the entire common bile duct showed squamous metaplasia. Besides, an invasive squamous cell carcinoma was found, stage pT3pN0. A next generation sequencing assay covering 315 tumor‐related genes revealed gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…After encountering the case reported here, we reviewed the clinical features and treatment options for biliary SCC. Knudsen et al [ 28 ] reported that alterations in FBXW7, CREBBP, CTCF, FAT1, MAGI2, MLL2, and NOTCH1 can predict the risk of extrahepatic biliary SCC.…”
Section: Discussionmentioning
confidence: 99%
“…After encountering the case reported here, we reviewed the clinical features and treatment options for biliary SCC. Knudsen et al [ 28 ] reported that alterations in FBXW7, CREBBP, CTCF, FAT1, MAGI2, MLL2, and NOTCH1 can predict the risk of extrahepatic biliary SCC.…”
Section: Discussionmentioning
confidence: 99%